Energy Consumption Analysis on Ginger Extract Powder Mixer Machine - Sarwi Asri; Prima Astuti Handayani; Djuniadi Djuniadi; Hanif Hidayat; Aditya Maulana; Muhammad Zhafran Dewantara; Siti Thoifatun Najiah (Universitas Sultan Ageng Tirtayasa, 2024)
Ginger extract powder is a popular product in the beverage and health industry, requiring careful processing to produce high-quality results. This study aims to determine the efficiency of the stirring blade design on the ginger extract powder stirring machine. The intensive stirring process can lead to faster wear of the blades, making the selection of suitable materials crucial. The research was conducted through direct observation at UKM Bekti Pertiwi. The data collection process was structured to capture both quantitative data: 1) Energy consumption: energy used by the machine was measured in kilowatt-hours (kWh) using a standardized electricity meter, and 2) Cycle time: the time for a full cycle was recorded, from material input to the completion of the stirring process. A controlled sample of 2 kg of ginger essence was used in each test to standardize conditions and ensure consistent results. The sample size was chosen based on typical batch sizes processed by SMEs, aiming to represent common production volumes. The ginger essence sample was prepared with a standardized consistency and viscosity to reduce variability and ensure repeatability across tests. The stirring blade samples were manufactured from stainless steel with a Teflon coating, selected due to its corrosion resistance and durability in acidic environments. Blade dimensions were set to 504 mm in diameter and 3 mm in thickness, based on initial design research suggesting these dimensions as optimal for the desired mixing efficiency and wear resistance. Each test was conducted under the same operational settings, including motor speed and cycle duration, to maintain uniformity in testing conditions. Results indicate that a combination of stainless steel and Teflon in the stirring blades provides optimal performance, with energy consumption reaching 0.1072 kWh for 2 kg of ginger extract. The electricity cost for one production cycle is IDR 144.93. These findings can be used for future production planning, as well as to improve operational efficiency and the quality of ginger extract products.